Luminosity function of high-z object candidates at the epoch of reionization (z 6) in cosmic evolution survey (COSMOS) field - N. Thananusak (2020)
© Published under licence by IOP Publishing Ltd. The investigation of the luminosity functions (LF) of objects at the epoch of reionization or EoR (z 6) is crucial for placing stronger constraints on the contribution of different ionizing photon sources. In this study, we aim to estimate the luminosity functions of z 6 candidates. The data catalog obtained from Hyper Suprime-Cam Strategic Program (HSC-SSP) ultra-deep survey data released one and the ultra-deep Visible and Infrared Survey Telescope for Astronomy (UltraVISTA) data released four in optical (rizy) and near-infrared (YJHKs) photometry filters, respectively. We focus the deep survey on Cosmic Evolution Survey (COSMOS) field, centered at RA ∼ 10h00m28.6s DEC ∼ +2°12′21.0″. The 79 candidates are selected by the Lyman Break Galaxies (LBGs) technique with z band drop-out, and photometric redshift approximation (photo-z). We then used the candidates to calculate the z 6 LF. Accordingly, we compare the LF with other works that focus on the high-z objects at similar z-range.